Laboratory deposition apparatus to study the effects of wax deposition on pipe magnetic field leakage signals - Karim, M.F.A. (EDP Sciences, 2014)
Accurate technique for wax deposition detection and severity measurement on cold pipe wall is important for pipeline cleaning program. Usually these techniques are validated by conventional techniques on laboratory scale wax deposition flow loop. However conventional techniques inherent limitations and it is difficult to reproduce a predetermine wax deposit profile and hardness at designated location in flow loop. An alternative wax deposition system which integrates modified pour casting method and cold finger method is presented. This system is suitable to reproduce high volume of medium hard wax deposit in pipe with better control of wax deposit profile and hardness. Â© 2014 Owned by the authors, published by EDP Sciences.